2009
DOI: 10.1111/j.1528-1167.2008.01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of cobalt‐induced hippocampal epileptiform discharges

Abstract: SUMMARYPurpose: To explore the cellular mechanisms of cobalt-induced epileptiform discharges in mouse hippocampal slices. Methods: Hippocampal slices were prepared from adult mice and briefly exposed to a CoCl 2 -containing external solution. Population and single cell activities were examined via extracellular and whole-cell patch recordings. Results: Brief cobalt exposure induced spontaneous, ictal-like discharges originating from the CA3 area. These discharges were suppressed by anticonvulsants, gap junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 73 publications
(111 reference statements)
1
19
0
Order By: Relevance
“…However, for patients with focal cortical dysplasia lesions, the authors found a positive correlation between Panx1 expression levels and the frequency of seizures that the patients had before surgery [73], suggesting the involvement of Panx1 in the epileptogenic process. Similar upregulation of Panx1 expression levels were obtained using mouse hippocampal slices subjected to Co 2+ [74], an in vitro model of epileptiform-like activity [75]. In this in vitro study, the authors found a two-fold increase in the glycosylated form of Panx1 and no change in Panx2 expression levels within 2 hours after Co 2+ exposure [74].…”
Section: Pannexin1 and Epileptic Seizure Activitysupporting
confidence: 71%
“…However, for patients with focal cortical dysplasia lesions, the authors found a positive correlation between Panx1 expression levels and the frequency of seizures that the patients had before surgery [73], suggesting the involvement of Panx1 in the epileptogenic process. Similar upregulation of Panx1 expression levels were obtained using mouse hippocampal slices subjected to Co 2+ [74], an in vitro model of epileptiform-like activity [75]. In this in vitro study, the authors found a two-fold increase in the glycosylated form of Panx1 and no change in Panx2 expression levels within 2 hours after Co 2+ exposure [74].…”
Section: Pannexin1 and Epileptic Seizure Activitysupporting
confidence: 71%
“…These events have been referred to as epileptiform burst discharges and have been widely studied to gain insight into the mechanisms underlying epileptiform activity. Historically, CA3 epileptiform burst discharges were produced in tissue removed from normal rodents by electrical stimulation (Stasheff et al 1985), chemoconvulsants such as cobalt, penicillin, kainic acid, tetanus toxin, pilocarpine, bicuculline, and picrotoxin (Dichter & Spencer, 1969; Schwartzkroin & Prince 1977; Wong & Traub, 1983; Fisher & Alger, 1984; Swann & Brady, 1984; Ault et al 1986; Müller & Misgeld, 1991; Nagao et al1996; Rutecki &Yang, 1998; He et al 2009), or perturbation of the neuronal environment by manipulating concentrations of extracellular ions (e.g. Cl - , K + , Mg 2+ , and Ca 2+ ; Schwartzkroin & Prince, 1978; Walther et al 1986; Traynelis & Dingledine, 1988; Perreault & Avoli, 1991; Jensen & Yaari, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Recent development in DNA/RNA sequencing technologies simplified study of genetic alterations in MCDs and LNETs on a tissue-wide scale. While some studies concentrated on comparison of tens to hundreds of selected genes from microdessected heterotopic neurons, atypical ganglion cells and astrocytes from FCD and GG 61,62 showing that there was a differential expression in glutamate and GABA receptors, and selected growth factors between the cells in tumor or malformation affected area and cells from control tissues, latter studies used either microarrays or RNA sequencing to interrogate global expression profiles and chromosomal reorganization in LNETs, low grade gliomas and TSC 14,[63][64][65][66][67][68][69][70][71] . Selective sequencing can still be applied to discover mutations in known malformations associated genes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Those studies concentrated on discovery of additional somatic postzygotic mutations and chromosome reorganization in LNETs and MCDs, while few of them has also reported on increased inflammatory response and activation of complimentary cascade in GG 69 and in TSC 63,68 . Interestingly Stone et al 64 used RNA expression profile and DNA methylation profile in LNETs (GG, DNETs, and with uncertain histologic type) to show that most of those segregate into two distinct groups, one group with astrocytic differentiation and is driven by BRAFV600E mutation and the second group had oligodendroglial differentiation and driven by FGFR1 mutation.…”
Section: Introductionmentioning
confidence: 99%